Neuro-ophthalmologic manifestations of corona virus disease (COVID-19): A case series (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
Manifold neuro-ophthalmological signs & symptoms have been described in association with corona virus disease 19 (COVID-19). These presenting manifestations probably due to the result of a range of pathophysiological mechanisms throughout the course from acute illness to recovery phase & late recovery phase. Optic nerve dysfunction like optic neuropathy is associated with post COVID-19 infection. In this case series we want to highlight about the course, sequelae & association of optic neuropathy in COVID-19 patients.BSMMU J 2021; 14 (COVID -19 Supplement): 42-44